PENGARUH MODEL PEMBELAJARAN PBL BERBANTUKAN GAME ULAR TANGGA TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 02 LUBUK BUAYA KOTA PADANG - Fahren, Muhammad Iqra; Meizartri, Ranti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of implementing the Problem Based Learning (PBL) model assisted by the snakes and ladders game on the IPAS learning outcomes of fifth-grade students at SDN 02 Lubuk Buaya, Padang City. This research is an experimental study using a sample of class V.B as the experimental class and V.C as the control class. Data collection techniques included pretests and posttests. The results of the posttest showed that the experimental class achieved an average score of 81.55, which was higher than the control class average of 71.67. This indicates that the use of the PBL model assisted by the snakes and ladders game significantly improves student learning outcomes..